2019
DOI: 10.1101/710426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Laminar differences in responses to naturalistic texture in macaque V1 and V2

Abstract: Most single units recorded from macaque V2 respond with higher firing rates to synthetic texture images containing "naturalistic" higher-order statistics than to spectrally matched "noise" images lacking these statistics. In contrast, few single units in V1 show this property. We explored how the strength and dynamics of response vary across the different layers of visual cortex by recording multiunit and gamma band activity evoked by brief presentations of naturalistic and noise images in V1 and V2 of anesthe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 45 publications
4
6
0
Order By: Relevance
“…First, we measured the entire neuronal response (40 - 200 ms from image onset) and calculated a modulation index to quantify response differences between different image types (Methods). Consistent with previous studies 11,14 , we found no significant difference between the magnitude of responses to NTIs and to SMNIs (, p = 0.67, paired t-test). However, the neuronal responses to natural images were consistently larger than those to NTIs (, p < 10 −31 , t-test) and to SMNIs (, p < 10 −42 , paired t-test).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…First, we measured the entire neuronal response (40 - 200 ms from image onset) and calculated a modulation index to quantify response differences between different image types (Methods). Consistent with previous studies 11,14 , we found no significant difference between the magnitude of responses to NTIs and to SMNIs (, p = 0.67, paired t-test). However, the neuronal responses to natural images were consistently larger than those to NTIs (, p < 10 −31 , t-test) and to SMNIs (, p < 10 −42 , paired t-test).…”
Section: Resultssupporting
confidence: 92%
“…Our results integrate two lines of work on natural image representation in V1 in the same experiments. On the one hand, consistent with previous studies on natural texture images 14,17,18 , our results show that single V1 neurons does not show significant selectivity to naturalistic textures. Specifically, V1 neurons do not show response differences between naturalistic textures and spectrum-matched noise images even with a large population of simultaneously recorded V1 neurons.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations